Quality Systems in the Food Industry - Fiorino, Marco; Barone, Caterina; Barone, Michele; Mason, Marco; Bhagat, Arpan (Chemistry of Foods, 2019)
This book explains the role of food-oriented (or 'food-centric') quality system standards in the modern food and beverage industry. It discusses food safety schemes based on the international norm ISO 9001 and the "Hazard Analysis and Critical Control Points" approach, and also introduces the new Global Standard for Food Safety (GSFS) and the International Featured Standard (IFS, 7th ed.), outlining standardization for international equivalence (while maintaining the necessary flexibility and independence - which is not always easy an easy task). Providing selected specific examples, it examines the problems of chemical additives and possible cross-contaminations between different production lines, as well as adequate reactions to and handling of intentional adulterations. In addition, it includes a chapter focusing on quality audits and technical data sheets in the food industry, and a final chapter describing the certification of food-grade lubricants in the food industry, especially with regard to allergenic substances.